2022
DOI: 10.2174/1874471014666210426111806
|View full text |Cite
|
Sign up to set email alerts
|

Ferulago angulata as a Good Radioprotector Against Genotoxicity

Abstract: Introduction: Natural products can be used as radioprotector agents because of containing phenolic compounds and several flavonoids with antioxidant properties. When the normal cells are exposed to ionizing radiation, they generate free radicals and reactive oxygen species that can cause damage in DNA, which leads to cellular dysfunction or even cell death. However, it is necessary to identify new radioprotective agents to protect normal cells. Ferulago angulata (F.angulata), a medicinal plant, can be used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Previous studies indicate Ferulago angulate decreases MDA levels in serum through increasing antioxidant capacity 26 . Amifostine is used for radioprotection in human as the only FDA‐approved drug, but side effects (such as hypotension, nausea, and vomiting) restricted its use in patients during exposure to IR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicate Ferulago angulate decreases MDA levels in serum through increasing antioxidant capacity 26 . Amifostine is used for radioprotection in human as the only FDA‐approved drug, but side effects (such as hypotension, nausea, and vomiting) restricted its use in patients during exposure to IR.…”
Section: Resultsmentioning
confidence: 99%
“…First, 50—200 μM of bio‐nanocomposite and 70 μl of FRAP reagent were incubated at 37°C for 5 min and absorbance was observed. The FRAP values and standard curve were shown in micromoles per liter (μM) and millimole Fe 2+ , respectively 24 …”
Section: Methodsmentioning
confidence: 99%
“…Treatment with Zn increased CAT and SOD activity and decreased MDA level in rats suffering from kidney oxidative stress induced by cadmium [50]. The electromagnetic radiation-induced oxidative stress via decreasing GSH and increasing MDA in kidney and plasma of rats, and the treatment with zinc mitigated the oxidative stress [15,17,51,52]. Treatment with another antioxidant agent such as carnitine in irradiated animals reduced the oxidative stress potential of radiation in lung and liver as vital organs and improved their function in comparison to the untreated group [46].…”
Section: Discussionmentioning
confidence: 99%
“…Kidney is an IR sensitive organ because the function and morphology of kidney as well as phenotype of kidney cells are affected by IR [12]. Several investigations have reported the protective effects of antioxidants scavenging free radicals as radio protectors [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Moshafi et al assessed the radioprotective effects of F. angulata on human blood lymphocytes. Their findings demonstrated that the 200 μg plant protected the cells from oxidative damage and gene toxicity, as demonstrated by a decrease in MDA and micronuclear frequency and an increase in superoxidase enzyme levels[106]. Similarly, Seyedi et al demonstrated that a bionanocomposites of Chitosan-Co-Silver complex synthesized from F. angulata as a reducing agent, decreased MN frequency of human lymphocytes exposed to ionization radiation, possibly due to its antioxidant activity[107].…”
mentioning
confidence: 97%